Corporate Capital Structure in Europe The Role of Country, Industry and Firm Size - Gostkowska-Drzewicka, Magdalena; Gostkowska-Drzewicka, Magdalena; Koralun-Bereźnicka, Julia; Majerowska, Ewa (Taylor & Francis Routledge [Imprint], 2024)
This book offers a comprehensive examination of the factors affecting corporate capital structures across 12 European Union countries, focusing on the influence of country-specific, industry-specific and firm-size-related determinants. It provides a comprehensive review of various interpretations of the capital structure concept and offers a detailed characterisation of commonly employed metrics. Furthermore, it offers an overview of capital structure theories and attempts to classify the factors that shape the financial leverage of enterprises within the framework of these theories. Additionally, it draws readers' attention to contemporary factors potentially affecting corporate financing decisions, such as Environmental, Social and Governance (ESG) considerations or technological advances and innovations in finance. It combines theoretical insights with empirical research to explore the direct and indirect impacts of these factors on companies' financing patterns. Targeting a broad readership including students, Ph.D. candidates, researchers, academics and financial practitioners, the book offers a rich understanding of capital structure optimisation and its significance for enhancing company value. Through its coverage of various capital structure theories, determinants and the role of external and internal factors in capital structure decisions, the book is an essential resource for those interested in the complex nature of these influences within the European landscape.
eng
Keywords: Accounting; Banking; Corporate finance; Economics, Finance, Business and Management; Economics; Finance and accounting; Finance and the finance industry; Financial accounting; Macroeconomics; Capital structure; Capital structure theories; Financial liquidity; Long and short-term debt; Panel data models; Trade-off theory; Value maximisation